Judicial waves, ethical shifts: bankruptcy courts and corporate ESG performance - Zhou, Zixun (Journal of business ethics, 2025)
Leveraging the staggered introduction of specialized bankruptcy courts across China as an exogenous shock, this study examines the impact of specialized bankruptcy courts on corporate ESG performance. Using listed firms in China from 2015 to 2021, we find that the introduction of specialized bankruptcy courts leads to an increase in corporate ESG performance. Our main results remain robust after considering endogeneity concerns and TWFE bias. The underlying mechanism is that these courts strengthen creditor protection, thereby enhancing access to bank loans for local firms. Moreover, this effect is more pronounced in firms with limited access to bank financing and in cities with more efficient legal and financial environments. Collectively, our study contributes a novel perspective to the discourse in law and finance, underscoring the broader implications of judicial reforms on corporate ethical behavior.